Analysis of metagenomic data reveals common features of halophilic viral communities across continents. (10th December 2015) - Roux, Simon; Enault, Francois; Ravet, Viviane; Colombet, Jonathan; Bettarel, Yvan; Auguet, Jean‐Christophe; Bouvier, Thierry; Lucas‐Staat, Soizick; Vellet, Agnès; Prangishvili, David; Forterre, Patrick; Debroas, Didier; et al.
Summary: Microbial communities from hypersaline ponds, dominated by halophilic archaea, are considered specific of such extreme conditions. The associated viral communities have accordingly been shown to display specific features, such as similar morphologies among different sites. However, little is known about the genetic diversity of these halophilic viral communities across the Earth. Here, we studied viral communities in hypersaline ponds sampled on the coast of Senegal (8–36% of salinity) using metagenomics approach, and compared them with hypersaline viromes from Australia and Spain. The specificity of hyperhalophilic viruses could first be demonstrated at a community scale, salinity being a strong discriminating factor between communities. For the major viral group detected in all samples (Caudovirales), only a limited number of halophilic Caudovirales clades were highlighted. These clades gather viruses from different continents and display consistent genetic composition, indicating that they represent related lineages with a worldwide distribution. Non‐tailed hyperhalophilic viruses display a greater rate of gene transfer and recombination, with uncharacterized genes conserved across different kind of viruses and plasmids. Thus, hypersaline viral communities around the world appear to form a genetically consistent community that are likely to harbour new genes coding for enzymes specifically adapted to these environments.